Transition from monitoring and assessment to self-monitoring and self-assessment - Valentina Pagani (Firenze University Press, 2020)
In line with the targets set by the Europe 2020 strategy (EC, 2010), by giving the student a central role, the research focus shifts to self-monitoring and self-assessment, two related components in a cyclical process (McMillan & Hearn, 2008). The research primarily aims to verify how students self-monitor and self-assess their learning process. Once outlined in their modalities, the research wants to dwell and reflect on the personal traits of students about two variables: area of ​knowledge and academic year. The subjects who took part in the questionnaire were 180 attending students, enrolled in the three-year degree courses in Education and Philosophy of the University of Padua, Verona, and Venice. The research aims to answer three research questions: 1) How is the self-monitoring process complementary to the self-assessment one? 2) Is there a correlation in the area of ​​knowledge of the students? 3) Is there a correlation in the academic year of students?   Transizione da monitoraggio e valutazione ad auto-monitoraggio e auto-valutazione In linea con gli obiettivi previsti dalla strategia Europa 2020 (EC, 2010), dando un ruolo maggiormente centrale allo studente, il focus della ricerca si sposta all'auto-monitoraggio e all'auto-valutazione, due componenti correlati in un processo ciclico (McMillan & Hearn, 2008). La ricerca vuole in primis verificare in che modo gli studenti auto-monitorano e auto-valutano il loro processo di apprendimento. Una volta delineate le loro modalità, la ricerca vuole soffermarsi e riflettere sui tratti personali degli studenti in relazione a due variabili: area di conoscenza e anno accademico. I soggetti che hanno preso parte al questionario sono stati 180 studenti frequentanti, iscritti ai corsi di laurea triennale in Scienze dell'Educazione e Filosofia delle Università di Padova, Verona e Venezia. La ricerca si prefigge di rispondere a tre domande di ricerca: 1) In che modo il processo di self-monitoring è complementare a quello auto-valutativo? 2) Vi è correlazione nell'area di conoscenza degli studenti? 3) Vi è correlazione nell'anno accademico degli studenti?